Why Do Populist-Outsiders Get Elected? A Model of Strategic Populists - Sebastian Miller (Inter-American Development Bank (IDB), 2011)
The existence of populist regimes led by outsiders is not new in history. In this paper a simple framework is presented that shows how and why a populist outsider can be elected to office, and under what conditions he is more likely to be elected. The results show that countries with a higher income and wealth concentration are more likely to elect populist outsiders than countries where income and wealth are more equally distributed. It is also shown that elections with a runoff are less likely to bring these populist outsiders into office.
Keywords: D72; D31; 330